Remittances in Russia and Caucasus and Central Asia : the Gravity Model - Poghosyan, Tigran (Washington, D.C. : International Monetary Fund, 2020)
Remitances are an important source of external financing in low- and middle-income countries. This paper uses the gravity model to analyze remittance flows in Russia and Caucasus and Central Asia (CCA) countries. Standard gravity determinants, such as GDP in sending and recieiving countries, bilateral distance, existence of common borders and common official language, fit remittance flows well. Remittances also react to inflation and exchange rate movements in recipient countries to sustain their purchasing power. In line with the altruism hypothesis, remittances flow to countries with higher age dependency ratio. Remittances are countercyclical and help stabilize outputs in recipient countries. However, global shocks resulting in sharp output losses of sending countries would lead to large volatility and decline of remittance inflows in recipient countries. The results of the analysis can be used to assess the impact of the COVID-19 shock on projected remittance flows into CCA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet